The effect of combined administration of ethanol and gabapentin on electricalnactivity of the cerebral cortex neurons in Wistar rats - L. G. Kolik; S. N. Kozhechkin (LLC "Publisher OKI", 2018)
Resume. Background. Today the search for drugs for alcoholism treatment is concentrated around substances with anticonvulsant action, which not only stop convulsive syndrome, but also contribute to the extension of the remission period during alcohol withdrawal. Despite the successful experience in the alcoholism treatment with structural analog GABA gabapentin, there is no convincing evidence of gabapentin interaction with GABA-ergic system in the brain, moreover, most results were obtained in vitro. The aim of the present work was to study mechanism of gabapentin action on CNS and its interaction with ethanol using electrophysiological methods in vivo. Methods. The effect of gabapentin on electrical activity of neurons in the frontal cortex of rats was studied with the microelectrode technique in adult male Wistar rats. Results. Gabapentin after systemic administration, 25-100 mg/kg, i.p., dose-dependent reduced the frequency of action potentials (AP) of neurons, without changing amplitude and shape of AP of neurons. When assessing changes in the frequency of extracellular exhaust AP at microiontophoretically summing gabapentin it is established that the drug reduced the frequency of АP in 15 of 23 neurons (p < 0.05), and increased GABA-induced inhibition of pulsed electrical activity of neurons in the frontal cortex. Gabapentin didn't affect the magnitude of exiting responses on ethanol supplied to neurons, however, increased (p < 0.05) inhibitory responses caused by ethanol in all 45 of the cells studied. Conclusion. The obtained data suggest that gabapentin has an allosteric effect on postsynaptic GABA receptors and increases ethanol-induced inhibition of neurons of the frontal cortex.